The implementation of social network analysis in disaster management at Sumber Maron - Muhammad Danang Setioko; Ayu Fitriatul 'Ulya (Universitas Merdeka Malang, 2024)
Social networks are certainly crucial in social life, ranging from family environments, education, work, to society as a whole. Sumber Marron is a tourist attraction located in Adi Luwih Hamlet, Karangsuko, Pagelaran, Malang. This tourist destination is highly popular among people of all ages, from students to adults. Given its popularity, unwanted incidents may occur. This research aims to examine the social networks of visitors and the management in the event of a disaster. The methods used are Social Network Analysis. The results of the analysis show that visitors of Sumber Maron have more interactions with the other visitors compared to rescue personnel in the event of an accident at the tourist site.